Study of importance of medial cortex in distal femur comminuted fracture - Kalariya, Mayur K.; Patel, Ankit R.; Lathiya, Dhruvik K. (International Journal of Research in Orthopaedics, 2022)
Background: Distal femur fractures require high energy trauma by means of road traffic accidents. There are various modalities of fixation, involving plating, external fixator and intramedullary nailing. cause of nonunion like smoking, osteoporosis, early weight bearing, improper construction of fixation, improper reduction. Methods: The study was conducted on 20 patients having distal femur fractures operated previously by using a different modality of implant goes in failure like bending of implant, broken of implant, peri implant fracture after second episode of trauma. Patient was preoperatively assessing for rule out occult low grade infection by blood investigation like ESR and CRP. Previous X-ray review to find cause of nonunion. Results: All patients showed a complete union at the fracture site with an average duration of 4-6 months. There was no complaint of infection, joint stiffness or difficulty in weight bearing after treatment with revision fixation and bone grafting. Patients were able to walk without affecting their daily activity of living. Conclusions: Comminuted medial cortex left unfixed or maligned will go into varus collapse and leads to failure of fixation.